U. Parvum serovars exhibit distinct pathogenicity in Chinese women of childbearing age: a multicentre cross-sectional study - Yingxuan Zhang; Wei Qing; Wenyu Mo; Rongdan Chen; Zuyi Zhou; Yi Hou; Yiya Shi; Cancan Qi; Jinxia Ou; Longxu Xie; CALM 2004 Study Group; Yifeng Wang; et al. (BMC Infectious Diseases, 2024)
Abstract Background Ureaplasma spp. can be classified into different serovars. It is unknown whether distinct serovars are associated with clinical signs and symptoms. Methods We conducted a multicentre cross-sectional study. U. parvum serovars were identified on the basis of their multiple-banded antigen (MBA) genes. After adjusting for demographic variables and other reproductive tract infections, the odds ratio (OR) and 95% confidence interval (CI) were calculated to determine the impact of U. parvum serovars on clinical symptoms. Results Among 5,277 individuals, U. parvum serovars 3 and 6 were the most prevalent serovars (17.9% and 16.0%, respectively). Potential confounders, such as age, body mass index (BMI), ethnicity, education level, contraceptive methods, number of sexual partners, gravidity, parity, and other sexually transmitted infections (STIs) that are associated with clinical symptoms (P < 0.1) were adjusted for in the univariate analysis. U. parvum serovar 14 was strongly positively associated with certain clinical symptoms, including redness and swelling of the vaginal wall (crude OR: 3.53, 95% CI: 1.92–6.49; adjusted OR: 5.21, 95% CI: 2.56–10.58), cervical bleeding and swelling (crude OR: 3.89, 95% CI: 2.38–6.36; adjusted OR: 7.37, 95% CI: 3.82–14.23), and cervical ectropion (crude OR: 2.08, 95% CI: 1.25–3.45; adjusted OR: 3.04, 95% CI: 1.60–5.74). In contrast, U. parvum serovar 3 was negatively associated with a variety of clinical symptoms, whereas no correlations were detected between U. parvum serovars 1and 6 with clinical symptoms. Conclusions Different U. parvum serovars exhibit distinct correlations with clinical symptoms, suggesting that U. parvum serovars are pathogenically heterogeneous and that further differentiation of serovars may be necessary. Trial registration The study was registered with ClinicalTrials.gov ( https://www.clinicaltrials.gov ; ID: NCT04694495; Registration Date: 2021–01-05).